A methodology to analyse the angular, radial and regional porosities of a cylindrical packed bed of spheres - Bester, P.M.; du Toit, C.G. (Nuclear engineering and design, 2022)
•Vertical line-based approach to calculate angular, radial and regional porosities.•Methodology validated against analytical and published results.•Determine angular variation in porosity for cylindrical planes and wedges.•Determine radial variation in porosity for radial planes and wedges.•3D variation in porosity of angularly, radially and axially defined regions. This paper proposes a vertical line-based methodology for the calculation of the porosity of packed beds of spheres. The results for the overall porosity, angular variation in porosity and tangentially averaged radial variation in porosity obtained through the use of this methodology are compared with the results of pre-existing methodologies and found to be in very good agreement, validating the vertical line-based methodology. Building upon this; the angular wedge porosities and angular plane porosities; the radial variation in porosity at different angular planes and the tangentially averaged porosities; and the regional porosities and grid porosities were evaluated for seven packed beds with different sized diameter aspect ratios. From the evaluation of the porosity results for specific points throughout these packed beds, it was found that the vertical line-based methodology has the capability to provide a detailed analysis of the porosity of a packed bed. It is shown that dividing a packed bed into sections, based on axial height, radial range and angular range, can be employed in the calculation of the 3D variation in porosity throughout a packed bed.